Domestic violence and pregnancy in Ireland: women's routes to seeking help and safety - O'BRIEN GREEN, SIOBÁN BRIGID (Trinity College Dublin. School of Social Work & Social Policy. Discipline of Social Studies, 2020)
This PhD research study explores the factors associated with the disclosure of domestic violence (DV) and subsequent positive service utilisation during and after pregnancy by women in Ireland. The study aimed to address a research gap by interviewing women who have direct personal experience of DV during pregnancy and who had sought help. This was in order to understand and identify supports and enablers, in addition to barriers and inhibitors, which enhance and allow for, or detract from, safety and help seeking by women. The research employed a qualitative framework underpinned by feminist and intersectional methodologies and approaches. A study Conceptual Framework was developed to guide the study and to visualise and explain the interrelationship between elements examined and emerging from the research, in addition to structuring and guiding the data analysis. Eighteen women were interviewed, either during pregnancy, or up to approximately five years post-pregnancy for the study. Four key informants were also interviewed for their comments and insights on the study sample composition and preliminary study themes. For the purposes of the study, disclosure is defined as when a woman discloses that she is experiencing domestic violence and is referred, or self-refers, to domestic violence support service(s) (in a broad construal) or women's refuge at some point between conception and one year post-pregnancy. The study inclusion criteria allows for women whose pregnancy ended in a live birth, miscarriage or termination (abortion) to participate: nevertheless, all women who were interviewed had pregnancies that resulted in live births. Thematic analysis of the data was used to identify common themes and to relate findings to the study Conceptual Framework. Women reported multiple and serious physical and mental health problems during and after their pregnancies which they related to living in an abusive relationship. Findings suggest that a lack of screening for DV and poor continuity of care and trust building opportunities between health care professionals and women erodes potential for disclosure and reduces opportunities for help and safety seeking. Women reported that time pressured medical appointments, before and after the birth, in busy maternity hospitals lacking a sense of privacy, created barriers to disclosing DV. Clear signposting and visible resources indicating how to access specialist agencies and supports for DV in maternity care settings are a strong recommendation emerging from the study. Women self-referred in most cases to DV services, but time spent finding an appropriate service may have increased the risk women were exposed to in relation to DV. However, each positive professional or service contact seemed to re-enforce and support a sense of moving forward and stimulate additional help and safety seeking by women. Once women find, or are referred to, and access specialist DV services, including refuges, they are very satisfied with the support provided, especially migrant women who were interviewed for the study.
APPROVED
Keywords: Domestic violence; intimate partner violence; pregnancy; help, support and safety seeking